Vida humana e o crime de abortamento - Silva, Edilson Freire da (2010)
Main theme of this thesis is the illicit abortion and its flowing. The research intends to show the initial moment of human life, main point for the act of stopping pregnancy before fetus birth date and it can be treated as a penal illegal since first human signs. Facing the legality commencement, wishing the State to avoid abortion practice, it should be established, through written law, as guaranteed fundamental, the exact terms of the right of punishing, describing all penal requisites, facing commencement and prohibition through analogy. This research intends to show laws interpretation, through doctrine or court decision, which refers to human life protection since its beginning, dissecting penal form named abortion. In the Democratic State of Law, human life must be protected by the State since the first moment of its existence, right and life protection that can or cannot follow evolution and biological science but that will be always defended in the law interpretation